UPAYA PENINGKATAN HASIL BELAJAR PAI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE DUA TAMU DUA TINGGAL (DUTA DUTI) PADA KELAS VI DI SD NEGERI 07 TANJUNG PENYEMBAL KOTA DUMAI - Latifah Latifah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is do it because the result of learning religious education inslam grade VI students of SD Negeri007 Tanjung Penyembal, Dumai which still very low. This study aims to improve student learning outcomes.From the data analysis, there was an increase of both teacher activity, student activity, and student learningresult. The teacher activity at the 1st cycle meeting was 70% (good enough) and at the 2nd meeting increased10% to 80% (good). In the second cycle of the meeting 3 teacher activity scored 85% (very good) and at the 4thmeeting to 95% (very good). From cycle I to cycle II, teacher activity increased by 15%. The student activityactivity also increased from 1st cycle meeting I was 65% (enough) and at 2nd meeting increased 15% to 80%(good). In the second cycle of meeting 3 it increases 5% from 80% (good) to 85% (very good) and at meeting 4increases 10% from 85% (very good) to 95% (very good). Student learning outcomes also showed an increase,from the basic score score of 65 increased to 75,5 in the first cycle of 10,5 points increase then in cycle IIincreased to 90 on the second cycles increased 14,5 points. From the data analysis there is an increase bothfrom teacher activity, student activity, and student learning outcomes. It can be concluded that the Enhancementof the Two Guests Two Stay Learning Model. can improve learning outcomes religious education islam grade 6students SD 007 Tanjung Pengembal Dumai.